2017
DOI: 10.18632/oncotarget.21019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of epidermal growth factor receptor sensitizing mutations on outcomes of patients with non-small cell lung cancer treated with definitive thoracic radiation therapy: a systematic review and meta-analysis

Abstract: BackgroundTo determine if the presence of epidermal growth factor receptor (EGFR) sensitizing mutations improves tumor control and survival outcomes in patients with non-metastatic non-small cell lung cancer (NSCLC) who received definitive thoracic radiation therapy (TRT) with or without chemotherapy.Materials and MethodsWe searched MEDLINE for eligible comparative studies which compared the outcomes of patients treated with definitive TRT according to EGFR mutation status. Meta-analysis was performed using ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, this expected difference has not been observed in the results obtained in clinical trials. In a systematic review to explore the impact of EGFR-sensitizing mutations on the outcomes of patients with NSCLC treated with definitive TRT, [64] Soon et al identified 7 studies that included 537 patients with stage III NSCLC. Up to 45% of the patients in these studies had mutations in exon 19 and 21.…”
Section: Discussionmentioning
confidence: 99%
“…However, this expected difference has not been observed in the results obtained in clinical trials. In a systematic review to explore the impact of EGFR-sensitizing mutations on the outcomes of patients with NSCLC treated with definitive TRT, [64] Soon et al identified 7 studies that included 537 patients with stage III NSCLC. Up to 45% of the patients in these studies had mutations in exon 19 and 21.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor, a cell surface receptor, regulates cell proliferation, apoptosis, angiogenesis, adhesion, and motility through intracellular signaling and controls tumor progression [8]. Sensitizing EGFR mutations are the most common actionable driver mutations that may induce Tyrosine Kinase (TK) activation and phosphorylation of downstream pathways, resulting in aggravating cancer [9] [10]. In-frame deletions in exon 19 and point mutations in exon 21 (L858R) are the most common EGFR mutations [8].…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 , 7 , 8 , 9 , 10 , 11 In several studies, patients with EGFR‐mutant LA‐NSCLC were found to have shorter progression‐free survival (PFS) than those without EGFR mutations, 5 , 6 , 7 whereas another study showed that patients with LA‐NSCLC with EGFR‐sensitizing mutations had a trend toward improvement in the overall response rate (ORR) compared with patients without EGFR mutations, with no significant differences in relapse‐free survival (RFS) and overall survival (OS). 12 Most patients with inoperable stage III NSCLC would face loco‐regional and/or distant recurrences in the first 2 years following definitive CRT, 2 , 13 , 14 , 15 with the feasibility and clinical value of salvage local therapy remaining controversial. Metastasectomy or cranial radiation may provide clinical benefit for patients with isolated brain metastases (BMs) following definitive CRT, 16 , 17 whereas re‐irradiations are occasionally performed for patients with loco‐regional recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable differences in treatment response and pattern of failure may exist between definitive CRT‐treated patients with LA‐NSCLC with or without driver mutations 5–11 . In several studies, patients with EGFR‐mutant LA‐NSCLC were found to have shorter progression‐free survival (PFS) than those without EGFR mutations, 5–7 whereas another study showed that patients with LA‐NSCLC with EGFR‐sensitizing mutations had a trend toward improvement in the overall response rate (ORR) compared with patients without EGFR mutations, with no significant differences in relapse‐free survival (RFS) and overall survival (OS) 12 . Most patients with inoperable stage III NSCLC would face loco‐regional and/or distant recurrences in the first 2 years following definitive CRT, 2,13–15 with the feasibility and clinical value of salvage local therapy remaining controversial.…”
Section: Introductionmentioning
confidence: 99%